Treatment of Multiple Diastema with Fixed Orthodontic Appliance: Case Report - Ulfah, Khairiyah; Rifki, Ayudia; Rambe, Sarinah (Dentistry Faculty, 2024)
Background:A diastema is a gap or distance between two or more adjacent teeth. This condition can affect a person's appearance and confidence. Treatment in cases involving aesthetics can be treated by multidisciplinary approach, one of which is orthodontics.Case Report:A 13-year-old boy presented with chief complaints of gap at his front teeth. Intra oral examination showed multiple diastemas on the upper and lower teeth, minimal crowding on the mandibular anterior teeth, and flaring/proclination of the maxillary anterior teeth, class I molar relation on the right and left sides, class I canine relation on the right and left sides, low palate (34.5%), overbite 2.5 mm, overjet 5 mm and maxillary midline shifted to the left by 1 mm. Treatment was performed with Roth system fixed orthodontic appliances for diastema closure.Conclusion:The evaluation of the aetiology of the diastema is an important issue before starting any orthodontic correction. In caseof multiple diastema, treatment with fixed orthodontic is an excellent alternative for diastema closure, especially when the incisors are of normal color, shape and size.